Diagnóstico socioeconómico de los pequeños comerciantes ubicados en el sector Sur de las Malvinas en la ciudad de Guayaquil – Ecuador - González Caicedo, Paula Viviana (2023)
This research reveals the social and economic situation of small formal merchants located in the southern sector of the Malvinas in the city of Guayaquil, of great importance for the information obtained specifically from the situation among the owners of these small trade units located on Av. Ernesto Albán Mosquera. The methodology used was a mixed approach, with emphasis on the quantitative when using the statistical method; qualitatively it was essential for interpretation and analysis; The scope of the study was descriptive, the techniques used were surveys and interviews, the first applied to the owners of small businesses located in the study sector; and, the interviews directed to two old merchants of the area. The most relevant results were in the social field, the aspects on the education completed in upper basic by the majority, also related to the health care they receive from the Ministry of Public Health, through the sub centers and hospitals, since in majority they do not have social security from the IESS, only a little more than a quarter of respondents have voluntary or peasant insurance, the latter in the case of indigenous people. Economically, most work with their own resources, the largest expenses are food and education, in addition, and they do not have guarantees to access formal credit. The importance of the study lies in the attention offered from research based on the right to a dignified life.